0177 Enhancing student learning by combining problem-based learning and human patient simulation. (2nd November 2015) - Nash, Eleanor; Paladugu, Madhavi; Crowther, Jane; Dickinson, Mike; Pimblett, Mark; Lees, Lorna
Abstract : Background: Problem-based learning (PBL) and Human Patient Simulation (HPS) are teaching methods that actively involve and engage students in their learning. 1 These teaching modalities are utilised in Undergraduate Medical Education, yet they are used as separate entities in the learning process. Learning is enhanced when students are provided with the opportunity to apply their theoretical knowledge into simulated context. 2 By merging the teaching modalities together, it reinforces and develops students' existing knowledge, as well as enhancing the students learning experience. Methodology: Fourth-year medical students at Royal Preston Hospital have combined PBL and HPS during their paediatric placement. Each week the students have a simulated scenario related to the PBL case. Qualitative data on the students' experiences of the combined sessions has been obtained through weekly Turning-Point feedback and a focus group at the end of the paediatric rotation. Results/outcomes: The HPS sessions have been received positively from the students. Feedback identified that the students have found HPS has consolidated and reinforced their theoretical learning from PBL. Gaps in their knowledge become apparent during HPS that may not be revealed during PBL discussions. Knowing that there was HPS during PBL has been a motivation for learning. It has helped with their clinical work, giving the students more confidence on their paediatric placement. Additionally, feedback reveals that HPS has developed the students' non-technical skills, which would not have been possible with pure PBL. Conclusions and recommendations: Combining PBL with relevant HPS has the benefit of contextual application of learning which enriches the students' understanding and approach to the management of real life problems. Following the success of the combined sessions, HPS is now a regular feature for Paediatric PBL. The aim is to extend this programme into other specialities and other year groups at Royal Preston Hospital. References: Sohn M, Ahn Y, Lee M, Park, H, Kang, N. The problem-based learning integrated with simulation to improve nursing students' self-efficacy. Open J Nurs 2013;3:95–100 Steadman RH, Coates WC, Huang YM, Matevosian R, Larmon BR, McCullough L, Ariel, D. Simulation-based training is superior to problem-based learning for the acquisition of critical assessment and management skills. Crit Care Med 2006;34:151–157